2022
DOI: 10.4103/jfmpc.jfmpc_61_22
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and determinants of anterior cruciate ligament rupture among athletes practicing football in Jeddah Avenues 2020

Abstract: Background: Anterior cruciate ligament (ACL) tear is a common sport injury and one of the most serious sport injuries affecting non-professionals and professional athletes. It is most commonly torn during sports that involve sudden stops and changes in direction such as football. Objective: To measure the prevalence and determinants of anterior cruciate ligament rupture as well as assess knowledge about it among young adult athletes practicing football. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…In relation to educational level, the finding of this study represented that most of both groups were university educated. This agree with Alqarni et al,(2020) (26) , who reported that that most of their studied sample were university educated. As regarding to mechanism of injury the results revealed that about one third of the patients in the control and study groups their mechanism of injury was due to playing sports.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In relation to educational level, the finding of this study represented that most of both groups were university educated. This agree with Alqarni et al,(2020) (26) , who reported that that most of their studied sample were university educated. As regarding to mechanism of injury the results revealed that about one third of the patients in the control and study groups their mechanism of injury was due to playing sports.…”
Section: Discussionsupporting
confidence: 92%
“…These increased inflammatory markers may adversely prolong recovery following orthopedicrelated surgery or musculoskeletal injury. (26) so this study will evaluate the effect of implementing sleep hygiene guidelines on daily living activities for anterior cruciate ligaments reconstruction patients. Concerning socio-demographic characteristics of the studied patients.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, the prevalence of ACL injury was found to be 14.7%. 7 Similarly, in a previous study, 67.52% of the participants had ACL tears. 8 In 52.11% of cases, the semitendinosus tendon was used for anterior cruciate ligament reconstruction in the form of a tripled or quadrupled graft as reported by another study.…”
Section: Discussionmentioning
confidence: 68%
“…[4] The prevalence of ACL injury in Saudi Arabia varies depending on the population being studied, with rates reported to be as high as 26.2%. [5][6][7][8] Recent data for the average wait time for ACLR in Saudi Arabia was reported to be 6 months in 45.9% of patients (n = 39) to more than 6 months in 32.9% (n = 28). [8] However, the optimal timing for ACLR is still a matter of debate, and there is no consensus on the ideal time for surgery.…”
Section: Introductionmentioning
confidence: 99%